Evaluation of a lytic bacteriophage for bio-control of Salmonella Typhimurium in different food matrices - Thung, Tze Young; Lee, Epeng; Mahyudin, Nor Ainy; Anuradha, Karunakaramoorthy; Mazlan, Nurzafirah; Kuan, Chee Hao; Pui, Chai Fung; Mohamad Ghazali, Farinazleen; Mahmud @ Ab Rashid, Nor Khaizura; Rallon, Wendy Dayang; Tan, Chia Wanq; Radu, Son (2019)
In the present study, a Salmonella Typhimurium-specific bacteriophage designated as ST02, belonged to the Myoviridae family was isolated from retail meat samples. Host range determination showed that ST02 was capable of infecting other Salmonella strains with latent period of 15 min and burst size about 97 PFU/cell. ST02 was stable over a wide range of pH (4–11) and at the temperature ranging from 4 to 50 °C. A significant decrease (P < 0.01) in the bacterial counts (approximately 2 log cycles) was observed in different food matrices after storage at 4 °C for 72 h. Our findings demonstrated that bacteriophage ST02 can offer an environmentally-friendly antimicrobial intervention for reducing the risk of Salmonella contamination in retail food.